Необхідність врахування зміни кісткової тканини під дією високої температури при ідентифікації особи за спаленими кістковими залишками - Голубович, Леонід Львович; Зубко, Марія Дмитрівна; Голубович, А. Л.; Голубович, П. Л.; Golubovich, L. L.; Zubko, M. D.; Golubovich, A. L.; Golubovich, P. L. (My University, 2018)
Наводяться дані щодо змін кісткової тканини, що виникають під дією різних температурних режимів спалювання, які повинні враховуватись при ідентифікації особи за спаленими кістковими залишками. The modern period of life, accompanied by frequent military conflicts in different countries, natural disasters, man-made disasters, terrorist acts, etc., leads to the deaths of individual citizens or entire groups. All these cases require the identification of deceased persons, including forensic methods. Nowadays, the method of genomic fingerprinting is becoming increasingly popular, as the most accurate and effective.At the same time, as our practice of identifying the soldiers and civilians who perished in the east of Ukraine in the «ATO zone», sometimes only scorched bone remnants found after shelling of rocket launchers used by Russian mercenaries in the forensic medical examination. Material research: The long tubular bones of skeletons of people with traumatic causes of death were selected as the research material. In total, in the period from 1974 to 2002, we selected and investigated 100 hip, shoulder, large and small tibial and ulna, and radial bones. The ratio of male and female bones is 1: 1. The age of the dead ranged from 20 to 92 years.The study was the bones of the dead Caucasians, of different nationalities, but they were all residents of Ukraine. Conclusion. Our experimental data reflect the patterns and some differences in the changes of the studied bones and even their individual departments under the influence of high temperature. These data should be taken into account by forensic experts, especially in determining the physique, gender and death rate of persons in the process of identification.
The need to take into account changes in bone tissue under the action of high temperature when identifying an individual by scorched bone remains
Keywords: кісткова тканина; режими спалювання; ідентифікація особи; bone tissue; burning regimes; identification of a person